SURVEY PAPER: SOFTWARE AUTOMATED TESTING TOOL USING SYSTEMATIC LITERATURE REVIEW METHOD - Absharina, Dheanda; Fahirah, Fahirah; Agustina, Fenni (Jurnal Pilar Nusa Mandiri, 2020)
Software testing is one of the most important roles in successful software development. The increasing complexity of software development requires the development team to use automated testing tools to test the quality and functionality of the application. In software testing, choosing a testing tool must be appropriate and in accordance with the software to be tested. Using the Systematic Literature Review method, this research collects and analyzes previous survey papers from 2 keywords, "Comparative of Automated Software Testing Tools" and "A Critical Analysis of Automated Software Testing Tools" on Google Scholar with a span of 2010 - 2020. Results from papers collected through 5 stages of the SLR, resulting in 11 papers that were reviewed. From these 11 journals, obtained 5 automated testing tools that are often discussed, Selenium, QTP, TestCompelete, Watir, and Ranorex. The results of this study indicate that there is no software automatic testing tool that is truly perfect because every automated software testing tool has its own strengths and weaknesses and it is expected that the results of this study can help software testers in choosing automatic testing tools according to their needs.